Effects of cigarette package colors and warning labels on marlboro smokers' risk beliefs, product appraisals, and smoking behavior: a randomized trial - Matthew D. Stone; Melissa Mercincavage; E. Paul Wileyto; Andy S.L. Tan; Janet Audrain-McGovern; Andrea C. Villanti; Andrew A. Strasser (BMC, 2023)
Abstract Objective Plain packaging and graphic warning labels are two regulatory strategies that may impact cigarette risk beliefs and reduce consumption, but data are needed to better understand how smokers respond to such regulations. Methods Adult, daily, Marlboro non-menthol smokers (Red [n = 141] or Gold [n = 43]) completed a mixed factorial randomized trial. Participants smoked their usual cigarettes during baseline (5-days) and were randomized to receive cigarette packs with a warning label manipulation (graphic vs. text-only). Within each warning label condition, participants completed three within-subjects pack color manipulations (red, gold, plain), each lasting 15 days. Participants were blinded to the fact that all packs contained their usual cigarettes. Mixed-effects models examined between- and within-subject differences on risk beliefs, product perceptions, and smoking behavior. Results Warning type and package color did not impact cigarette consumption or subjective ratings. However, use increased in all conditions (2.59-3.59 cigarettes per day) relative to baseline. While smokers largely held correct risk beliefs at baseline (Mean = 6.02, SE = 0.17, Range:0-8), the cumulative number of incorrect or uncertain cigarette risk beliefs increased from baseline in all pack color manipulations in the text (IRR range = 1.70-2.16) and graphic (IRR range = 1.31-1.70) warning conditions. Across all pack color periods, those in the graphic (vs. text) warning condition had reduced odds of reporting their study cigarettes as 'safer' than regular cigarettes (OR range = 0.22-0.32). Conclusions Pack color modification may increase uncertainty about several key cigarette risk beliefs, though graphic warnings may attenuate these effects. Regulatory agencies could consider supporting policy changes with information campaigns to maximize public knowledge. Trial registration November 25, 2014; Registration number: NCT02301351.